HARMONY IN ARCHITECTURE AND THE LAW OF THE STRUCTURAL ORGANIZATION - , С. Г. (Municipal economy of cities (Technical science), 2013)
Are considered questions of the correlation организованности and chaos, ordering and varieties in architectural shaping.